Black woman protesting against the South African army's occupation of Soweto a.o. townships during the state of emergency in 1985. . See also box H12/714: Women's struggle in South Africa 2 - Weinberg, Paul,
Black woman protesting against the South African army's occupation of Soweto a.o. townships during the state of emergency in 1985. See also box H12/714: Women's struggle in South Africa 2.